Emergency Preparedness for Children with Autism Spectrum Disorder (ASD) in Yogyakarta - Indriasari, Fika Nur; Widyarani, Linda; Kusuma, Prima Daniyati (Jurnal Keperawatan Soedirman, 2018)
ABSTRACTIndonesia lies on the ring of fire and this includes Yogyakarta province which had experienced some earthquakes. The earthquake that occurred in 2006 caused thousands of people died. Most of the survivors were elderly people and children. Children are a vulnerable group, especially those with special needs. School is the first reference to teach earthquake disaster preparedness to children. This research used observational descriptive design. Purposive sampling technique was used, and data was collected through observation sheet. Respondents were with autism in Special School of Negeri Pembina Yogyakarta (n=23). Storytelling and Simulation on Earthquake Disaster Preparedness gave positive influence towards the mitigation ability by children with special needs, especially those with autism. There were nine children with autism in the category of low IQ, six in the category of average IQ and eight children in the category of superior IQ. Before the storytelling was conducted, children’s ability and involvement in the simulation was 35% (8 children). Conversely, the children’s ability and involvement raised to 78% (18 children) after being given five times (5x) simulation and storytelling. Storytelling and simulation method were effective as training methods in earthquake disaster mitigation on children with autism. There was 43% increase of mitigation level before and after intervention.ABSTRAKDaerah di Indonesia merupakan ring of fire dan Yogyakarta merupakan salah satu daerah yang mengalami gempa bumi. Gempa yang terjadi pada tahun 2006 menimbulkan banyak korban, mayoritas adalah orang lanjut usia dan anak-anak. Anak-anak merupakan kelompok rentan terlebih anak dengan berkebutuhan khusus. Sekolah sebagai tempat rujukan pertama untuk memberikan edukasi siaga bencana terhadap anak-anak.Desain penelitian adalah deskriptif observasional. Teknik pengambilan sampel dengan purposive sampel sedangkan teknik pengumpulan data dengan lembar observasi. Metode pengambilan sampel dengan purposive sampling. Responden yang mengikuti penelitian ini sebanyak 23 anak autis. Pemberian simulasi siaga bencana gempa bumi memberikan pengaruh positif terhadap kemampuan mitigasi anak berkebutuhan khusus dengan autis. Anak autis dengan kategori IQ rendah 9 orang, IQ sedang 6 orang dan IQ tinggi 8 orang. Sebelum diberikan pembelajaran story telling, kemampuan dan keterlibatan anak dalam melakukan simulasi sebanyak 35% (8 anak) namun setelah diberikan pembelajaran dan simulasi sebanyak 5x, kemampuan dan keterlibatan anak meningkat sebanyak 78% (18 anak). Metode simulasi efektif sebagai pembelajaran mitigasi bencana gempa bumi pada anak autis. Peningkatan kemampuan mitigasi sebelum dan sesudah diberikan pembelajaran sebanyak 43%.